2021
DOI: 10.1080/07853890.2021.2016942
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of Fn-induced high expression of KIR2DL1 in CD8 T lymphocytes in oesophageal squamous cell carcinoma

Abstract: Background To analyze the correlation between the inducing effect of Fusobacterium nucleatum (Fn) on the surface expression of the inhibitory receptor KIR2DL1 on CD8 + T cells in oesophageal squamous cell carcinoma (ESCC) and the clinicopathological features and survival prognosis and to explore its clinical significance. Methods The inducing effect of Fn on CD8 + T cell surface inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The OD 450 nm was determined by an enzyme-labeled instrument (PerkinElmer, USA). The PTX IC 50 for 24 h among different groups was calculated and compared. , Cells in each group were routinely cultured in 96-well plates at 1 × 10 3 cells/100 μL for 24 h. Ten μL CCK8 reactant was infused to each well. The OD 450 nm was determined by enzyme labeling (PerkinElmer, USA) every 24 h. The OD 450 nm of each group was compared to detect its proliferative ability in vitro …”
Section: Methodsmentioning
confidence: 99%
“…The OD 450 nm was determined by an enzyme-labeled instrument (PerkinElmer, USA). The PTX IC 50 for 24 h among different groups was calculated and compared. , Cells in each group were routinely cultured in 96-well plates at 1 × 10 3 cells/100 μL for 24 h. Ten μL CCK8 reactant was infused to each well. The OD 450 nm was determined by enzyme labeling (PerkinElmer, USA) every 24 h. The OD 450 nm of each group was compared to detect its proliferative ability in vitro …”
Section: Methodsmentioning
confidence: 99%
“… 61 In addition, co-culture experiments have revealed that F. nucleatum may increase CD8+ T cell, KIR2DL1 expression over time, thereby weakening the immune system’s response to cancer and reducing the sensitivity of tumor cells to cisplatin. 62 Pertaining to immunological aspects, a congruence has been discerned between F. nucleatum infiltration and the recruitment of Treg cells. Consequently, chronic F. nucleatum infection may contribute to the malignant progression of esophageal cancer by attracting Treg cells, thereby stifling immune responses, fostering tumor cell proliferation, facilitating immune escape, and ultimately engendering long-term colonization.…”
Section: F Nucleatum and Tumorigenesis Tumor Metastasismentioning
confidence: 97%
“…Wang et al. (2022) discovered that F. nucleatum induced a high expression of KIR2DL1 in CD8+ T cells, which decreased the CD8+ T‐cells’ ability to kill tumors.…”
Section: Fusobacterium Nucleatummentioning
confidence: 99%